Study on Establishing the Leg Size System of Vietnamese Women with Varicose Veins - Vu, Thi Hong Khanh; Tran, Pham Quynh Phuong (Old Journal, 2020)
The study used the leg sizes of 166 Vietnamese women aged 30 and older who were treated for varicose veins at Cho Ray Hospital and Transport Hospital 7 in Ho Chi Minh City to build a leg size system of patients, with the error of 1% and the accuracy of 99%. [cite: 10] By using SPSS software for data analysis, the study has built a leg size system of Vietnamese women suffering from varicose veins including 14 sizes according to two key parameters: Distance from butt to heel Dc and calf circumference Vbc. [cite: 11] According to Dc, the size system is divided into 5 sizes XS, S, M, L, XL separated by 2.5 cm. [cite: 12] Then, according to Vbc, the sizes XS, S, XL and L are divided into 3 small sizes and the XL size is divided into 2 small sizes, these small sizes spaced 1.5 cm according to Vbc. [cite: 13] Each small size is identified by 10 parameters: circumference of ankles, calves, knees, thighs, distance from buttocks to heels, distance from buttocks to ankles, distance from calves to ankles, distance from knees to heels, height and weight. [cite: 14] With 14 sizes, this size system serves more than 73% of Vietnamese women suffering from varicose veins. [cite: 15]